SYSTEMATIC LITERATURE REVIEW : "EKOSISTEM NIRKABEL UNTUK KOMPUTASI BERGERAK DAN M-COMMERCE: TINJAUAN LITERATUR SISTEMATIS TERHADAP TREN TERKINI, TANTANGAN KRITIS, SERTA PROSPEK INOVASI MASA DEPAN - Arafah, Zahid Nugrah; Veri, Jonh (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to analyze current trends, critical challenges, and future innovation prospects in the wireless ecosystem for mobile computing and m-commerce through a Systematic Literature Review (SLR) based on the PRISMA protocol. The literature search was conducted on the Google Scholar database, focusing on publications from 2020 to 2025, using keyword combinations such as "wireless," "mobile computing," "mobile commerce," and "future directions." From an initial collection of 100 articles, seven met the inclusion criteria and were analyzed in depth. The findings indicate that the wireless ecosystem and mobile computing are not merely technological trends but have become tangible instruments transforming various strategic sectors, including economy, finance, healthcare, education, and logistics. In the economic sector, m-commerce drives financial inclusion and supports the growth of MSMEs (Micro, Small, and Medium Enterprises) through digital platforms. In healthcare, wireless technology enables telemedicine and health monitoring via wearable devices. In education, e-learning and mobile learning enhance accessibility and learning quality. Furthermore, technologies such as 5G, IoT, and blockchain play crucial roles in improving system efficiency and security. However, challenges related to data security, privacy, interoperability, and the digital divide still need to be addressed. This study recommends the development of adaptive policies, investment in digital infrastructure, and further research to bridge existing gaps. The findings contribute valuable insights for researchers, practitioners, and policymakers in understanding the dynamics and future development of the wireless ecosystem